(untitled) (Лучшие интеллектуальные исследования, 2025)
This article discusses the idea of a dream job from an international perspective, highlighting global career trends, personal motivations, and the evolving nature of the workforce in the 21st century. The article provides insights into how young people around the world define and pursue their ideal careers, taking into account economic, technological, and social changes.